Experimental and simulation investigation of ultrasonic elliptical vibration cutting of tungsten alloys in ultra-precision machining - Sen Yin; Wai Sze Yip; Zhigang Dong; Renke Kang; Suet To (Journal of Materials Research and Technology)
Ultrasonic elliptical vibration cutting (UEVC) offers the benefits of extending tool life and enhancing surface finish, enabling ultra-precision machining of hard-brittle tungsten alloys. Exploring the effect of vibration directions on UEVC of tungsten alloys has important implications for an improvement of machining quality. In this study, the vibration factors of UEVC are investigated individually, and kinematic models of various Ultrasonic vibration cutting (UVC) are established. Finite element modeling (FEM) reveals that ultrasonic vibration can decrease the cutting force to varying degrees and increase the strain rate in the tungsten alloys cutting zone up to 1.8E5 s−1, with the effect of elliptical locus being the most prominent. Finally, an examination of the surface microstructures and chip formation of UVC on tungsten alloys reveals that it facilitates plastic material removal and increases material plasticity, which advances the understanding of the machining techniques utilized to achieve the ultra-smooth surface of tungsten alloys using UEVC.